Understanding School Dropout Decisions through Parenting Styles and Learning Motivation: Evidence from a Rural Indonesian Case Study - Siti Juariah; Halimah Halimah (Lentera Ilmu Nusantara, 2026)
This study aims to understand the relationship between parenting styles and children's learning motivation in Cilangkara Village, particularly in cases of school dropouts. This research employs a qualitative method with a case study approach, where data was collected through interviews and observations of school dropouts, their parents, and neighbors, allowing for an in-depth understanding of social and familial dynamics influencing learning motivation. The findings indicate that authoritative parenting increases children's learning motivation, while authoritarian and permissive parenting tends to decrease motivation, contributing to the decision to drop out of school, highlighting the theoretical relevance of parenting typologies in explaining motivational outcomes. Additionally, economic factors and negative experiences at school also influence children's decisions to lose motivation in continuing their education and provide practical implications for parents, educators, and local policymakers in designing context-sensitive educational interventions.